2021
DOI: 10.1128/spectrum.00519-21
|View full text |Cite
|
Sign up to set email alerts
|

The Human Innate Immune Protein Calprotectin Elicits a Multimetal Starvation Response in Pseudomonas aeruginosa

Abstract: Transition metal nutrients are critical for growth and infection by all pathogens, and the innate immune system withholds these metals from pathogens to limit their growth in a strategy termed “nutritional immunity.” While multimetal depletion by the host is appreciated, the majority of studies have focused on individual metals. Here, we use the innate immune protein calprotectin (CP), which complexes with several metals, including iron (Fe), zinc (Zn), and manganese (Mn), and the opportunistic pathogen … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 84 publications
(158 reference statements)
0
15
0
Order By: Relevance
“…Two separate studies reported that CP inhibits phenazine production by P. aeruginosa . , Fe depletion of culture medium had a similar effect to CP on phenazine levels, whereas depletion of Zn or Mn did not, suggesting that CP inhibits phenazine production in an Fe-dependent manner . The proteomic analysis of the effect of CP on the P. aeruginosa proteome also supported these findings; growth of P. aeruginosa under CP-treated and Fe-depleted conditions resulted in a downregulation of proteins involved in phenazine biosynthesis . The mechanism by which CP inhibits phenazine production is unknown.…”
Section: Fe(ii) Withholding By Calprotectin and Bacterial Responsesmentioning
confidence: 74%
See 3 more Smart Citations
“…Two separate studies reported that CP inhibits phenazine production by P. aeruginosa . , Fe depletion of culture medium had a similar effect to CP on phenazine levels, whereas depletion of Zn or Mn did not, suggesting that CP inhibits phenazine production in an Fe-dependent manner . The proteomic analysis of the effect of CP on the P. aeruginosa proteome also supported these findings; growth of P. aeruginosa under CP-treated and Fe-depleted conditions resulted in a downregulation of proteins involved in phenazine biosynthesis . The mechanism by which CP inhibits phenazine production is unknown.…”
Section: Fe(ii) Withholding By Calprotectin and Bacterial Responsesmentioning
confidence: 74%
“…Two prior studies reported that the P. aeruginosa siderophore pyoverdine is produced in elevated quantities in the presence of CP. , Subsequent proteomic analysis of the response of P. aeruginosa to CP demonstrated increased expression of proteins involved in pyoverdine-mediated Fe uptake . Moreover, PrrF sRNAs regulate an Fe sparing response in P. aeruginosa , and analyses of expression of the PrrF-regulated gene antR in response to CP indicated that Fe withholding by CP signals PrrF-mediated translational changes. ,, While these findings support CP-mediated Fe starvation and sparing responses in P. aeruginosa , the aforementioned proteomic analysis of P. aeruginosa indicated that CP did not effect many PrrF-dependent changes and thus appears to elicit an incomplete Fe starvation response . In particular, CP treatment did not affect expression of many Fe-containing metabolic proteins, such as TCA cycle enzymes SdhABCD and AcnB, which are normally downregulated by PrrF sRNAs upon Fe limitation .…”
Section: Fe(ii) Withholding By Calprotectin and Bacterial Responsesmentioning
confidence: 87%
See 2 more Smart Citations
“…Collectively, these iron-binding proteins sequester Fe to minimize toxicity and to purpose this trace metal for host cellular processes. In addition, these proteins along with other immune effectors, including hepcidin ( 4 , 5 ), ferroportin ( 4 , 6 ), and calprotectin ( 7 , 8 ), collectively act to limit Fe availability to invading microorganisms through a process termed nutritional immunity ( 9 , 10 ). Therefore, to successfully colonize and infect a host, an invading bacterial pathogen must overcome host-driven nutrient sequestration and acquire Fe to support growth in vivo ( 1 ).…”
mentioning
confidence: 99%